Crespos insurgentes, estética revolta memória e corporeidade negra paulistana, hoje e sempre - Silva, Célia Regina Reis da (2016)
This study raised and analysed issues related to kinky hair, understood as a territory of insurgencies in reexistence aesthetics in the decoloniality of bodies, beings and knowledges made invisible by the hegemonic Eurocentric cultural pattern. The research, carried out in the poor areas of São Paulo, focused on cultural collective movements, in which young Afro-Brazilians manifest themselves through Black and peripheral literary narratives and performances, with poetry readings, songs, plays, blogs, magazines, adornments, clothing, grafitti, tattoos, particularly kinky hairstyles in intercultural, intertextual and mediatic relations, expressing their Blackness, in a perspective of a “corporeal semiology”. They are current cultural identity practices in a productive dialogue with the past, in a continuous Afro diasporic struggle for culture and (self) representation in the racial relations of modernity